Restricted access information actualization in network resources - Самойленко, Денис Миколайович (Ukrainian Information Security Research Journal, 2015)
For including of restricted access information (RAI) in network information resource (NIR) especially for suchplaced in public, global and other open networks it isnecessary to organize additional security actions. Existing requirements prohibit RAI transfer through the open channels, but state no limitations for RAI placing in NIR parts – program codes, files, databases etc. In the presentwork the user and network resource interconnection scheme is proposed for restricted access information actualization. RAI does not exist in open form in everypart of scheme, except the last one – visualization. Authenticuser’s data is proposed to be divided onto two categories. Server part is constructed from three architecture layers. Integrity control is realized with secret distribution by different structural elements. Realization of theproposed scheme allows increasing of public NIR information security especially with RAI.